A telenursing application Innovation based on local wisdom in nursing care for chronic disease patients - Antia Antia; Setyowati Setyowati; Hanny Handiyani; Achmad Nizar Hidayanto (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Patients with chronic diseases generally experience repeated hospitalizations. Cultural diversity can affect communication and engagement from health care providers and recipients. An interactive culturally sensitive telenursing application is needed as a form of continuous nursing intervention when patients are at home. Purpose: To build and test the culturally sensitive telenursing application of Suster Kita. Method: Using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) process design. The research was conducted from August 2022 to February 2024 and tested on 20 respondents in the DKI Jakarta area. The evaluation of the effectiveness of the Suster Kita culturally sensitive telenursing application at the implementation stage was carried out using a questionnaire on the use of the application developed by the research team. The final results of the application are evaluated 2 weeks after the respondent uses the application. Results: the use of the application showed that the average knowledge of chronic diseases and their treatment consisting of 10 knowledge components increased before and after the trial of the use of the culturally sensitive application of Suster Kita. Conclusion: the intervention is acceptable to users and is worth using. Application suggestions are integrated with laboratory results.